2022
DOI: 10.3389/fneur.2022.987684
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nomogram for predicting acute kidney injury in patients with acute ischemic stroke: A retrospective study

Abstract: BackgroundThis study sought to develop and validate a dynamic nomogram chart to assess the risk of acute kidney injury (AKI) in patients with acute ischemic stroke (AIS).MethodsThese data were drawn from the Medical Information Mart for Intensive Care III (MIMIC-III) database, which collects 47 clinical indicators of patients after admission to the hospital. The primary outcome indicator was the occurrence of AKI within 48 h of intensive care unit (ICU) admission. Independent risk factors for AKI were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies reported the different risk models to predict AKI in patients with IS. Zhu et al developed a nomogram that includes blood urea nitrogen (BUN), creatinine, red blood cell distribution width (RDW), heart rate (HR), Oxford Acute Severity of Illness Score (OASIS), the history of congestive heart failure (CHF), the use of vancomycin, contrast agent, and mannitol and found that nomogram showed good predictive ability ( 34 ). For ICU patients, the SIRS, OASIS, APS III, SAPS II, and CCI scores are fundamental individualized risk assessments for characterizing disease severity and degree of organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the different risk models to predict AKI in patients with IS. Zhu et al developed a nomogram that includes blood urea nitrogen (BUN), creatinine, red blood cell distribution width (RDW), heart rate (HR), Oxford Acute Severity of Illness Score (OASIS), the history of congestive heart failure (CHF), the use of vancomycin, contrast agent, and mannitol and found that nomogram showed good predictive ability ( 34 ). For ICU patients, the SIRS, OASIS, APS III, SAPS II, and CCI scores are fundamental individualized risk assessments for characterizing disease severity and degree of organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have endeavored to construct a nomogram for AKI incidence in ischemic stroke patients using the Medical Information Mart for Intensive Care (MIMIC) III database [ 10 ]. Regrettably, this model relies on the Oxford Acute Severity of Illness Score (OASIS), which introduces clinical intricacy and restricts its broader applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, this model relies on the Oxford Acute Severity of Illness Score (OASIS), which introduces clinical intricacy and restricts its broader applicability. Moreover, the existing model solely forecast AKI within 48 h of ICU admission, lacking the ability to accurately predict AKI throughout the entire ICU stay [ 10 ]. Therefore, it is imperative to devise a simplified nomogram based on readily accessible clinical features, enabling prompt and effective assessment of the risk of AKI incidence during the ICU hospitalization of individuals with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%